Fundamentals of mental health nursing - Clarke, Victoria; Walsh, Andrew (Oxford University Press, 2009)
This is a case-based, service user-centred textbook for mental health nursing students to use throughout their pre-registration studies. The essential theory required for nursing care is explored alongside real service users' views and fictional cases